The significance of english language development for future Asian tourism and hotel management professionals. - Zou Jiahui (2019)
The existent research explores the significance of developing English at schools and universities, and the impact of ESP courses on the Asian Tourism and Hotel Management sector. It is suggested to teach ESP to students of intermediate-advanced English level. In this regard, future professionals can communicate in the target language worldwide and prepared to take ESP courses. It is also significant to contemplate the advantage of appropriate English fluency in the Tourism and Hotel Management sector and the disadvantages of not being fluent in this professional area. To have prepared Asian professionals, it is essential to apply Information and Communication Technologies (ICTs) to Develop English skills. Accordingly, countries such as Vietnam and Malaysia use ICTs to practice the target language using a technique called Digital Storytelling which boosts the development of this language. It is also essential to train English teachers in Asia since many non-English spoken countries attempt to develop English education through educational reforms. Consequently, English teachers are more and more crucial in educational institutions. As a result, if someone wants to become a teacher in South Korea they are required to attend education courses to obtain a teaching certificate. Moreover, having native speakers at schools enable learners to practice conversations in the target language. For this reason, SMOE declared that it would steadily invite more native speakers of English to every elementary and middle school to improve English communicative skills. The development of reading, writing, listening and speaking skills seek to improve the target language in Chinese universities. Listening and speaking practice improves the accent and produces more fluency for daily communication. On the other hand, reading and writing are combined to develop ample vocabulary and better spelling. Concerning the Importance of ESP in Malaysia, it was found that speaking was considered as having the most enormous significance. The increased evolution of this language in Asia has been caused because of demographics, economic change, technology and educational trends which have led Asians to seek for means to develop English conversational skills to have a competitive advantage in the labor market. Finally, ESP teaching for Asian students who major in Tourism and Hotel Management presents some advantages and disadvantages of having or not appropriate English communication fluency. These students strive to develop their communicative skills since customer service has the most significant impact on their future professions. On the contrary, not having appropriate English communication fluency in the Tourism and Hotel Management sector present some disadvantages to function efficiently in this area, such as independent traveler not able to hold a conversation with native speakers and not giving a good Airline Service Quality to customers. The authors of the present study recommend further research on the different teaching techniques that educators use in Asia to develop ESP that centers in Tourism and Hotel services.